Evolução da autonomia financeira dos municípios cearenses em um cenário de proposta de reforma tributária - Grangeiro, Virgílio Crescêncio (2017)
This study investigates the evolution of the financial autonomy of the municipalities of the State of Ceará in a scenario of tax reform proposal. The hypothesis underlying the study establishes that once the evolution of municipal autonomy has been confirmed, the municipal collecting authority should be maintained. The empirical exercise methodology is based on Unit Root tests for panel data between 2004 and 2016 on the ratio between revenues collected by municipalities and total resources transferred under constitutional terms. According to the results, there is a stagnation of the municipal financial autonomy in the state as a whole, even though there are areas with a representative evolution of the indicator used, such as the Metropolitan Region of Fortaleza (RMF), the South Center of the state and which involves the municipality of Sobral. Even with results indicating the seasonality of the municipal revenue in relation to the transfers received in several regions, the results verified in some developed nuclei of the state prove advances of the financial autonomy that do not justify the penalization anticipated to the Brazilian municipal administrations with the PEC of the tax reform in the terms.